2011
DOI: 10.1002/lary.21989
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous Cell Carcinoma in Pregnant Women

Abstract: Introduction:Head and neck squamous cell carcinoma (HNSCC) has traditionally been known as a disease of older men with a history of tobacco and alcohol abuse. Recently, though, the incidence of this disease has been increasing in younger patients, especially women. This subset includes pregnant women. The purpose of this study was to investigate HNSCC in pregnant women, a population that represents a rare but therapeutically challenging patient subset. Methods: After obtaining IRB approval, the EMERSE search e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…We identified thirty two cases of pregnant patients with tongue SCC following a literature search as shown in table 1, with the current patient included. 4,5,6,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26 We excluded cases reported as a regional recurrence of tongue SCC during pregnancy. Only one pregnant patient with SCC of the tongue in the published literature chose termination of pregnancy prior to treatment of the malignancy; however, publication bias must be considered when interpreting this.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We identified thirty two cases of pregnant patients with tongue SCC following a literature search as shown in table 1, with the current patient included. 4,5,6,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26 We excluded cases reported as a regional recurrence of tongue SCC during pregnancy. Only one pregnant patient with SCC of the tongue in the published literature chose termination of pregnancy prior to treatment of the malignancy; however, publication bias must be considered when interpreting this.…”
Section: Discussionmentioning
confidence: 94%
“…Mhallem Gziri et al reported on the use of adjuvant chemoradiation with cisplatin in a patient with tongue SCC during pregnancy without complication. 22 The patient reported in the current case received carboplatin due to its reported better toxicity profile compared to cisplatin in the context of pregnancy. 38 Doses of carboplatin up to an area under the curve of 7.5 have been shown not to be associated with significant placental transfer, fetal exposure or fetal toxic effects in an ex vivo study.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…Of those locally advanced tumors, 46.7% appeared in the first trimester of pregnancy. 9,12,15,17,18 Only 26.6% of these patients experienced local or regional recurrence, and all those patients died of local or metastatic evolution at 2 years. As an indirect comparison (thus to be taken with caution), the 5-year survival rate for a population of adults younger than 40 years old was 52.7% in the SEER database.…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…Usual risk factors such as tobacco or alcohol consumption were not found in patients presented in Table 1; only 1 patient had a 6 pack-year tobacco history. 9 Human papillomavirus (HPV) exposure is another known risk factor for HNSCC, and among these tongue and tonsil carcinomas. Though among the different cases showed in Table 1, the presence of HPV was only searched for four patients 9 and was negative.…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…Head and neck cancer (HNC) during pregnancy is rare, and the best management is challenging due to the conflict between maternal and fetal benefits [ 5 ]. A paucity of information in the medical literature exists regarding outcomes of radiation therapy, chemotherapy, and reported maternal and fetal outcomes.…”
Section: Introductionmentioning
confidence: 99%